2022
DOI: 10.7759/cureus.22722
|View full text |Cite
|
Sign up to set email alerts
|

Cadaveric Study on the Morphology and Morphometry of Heart Papillary Muscles

Abstract: IntroductionA normal atrioventricular valve complex of the heart consists of the atrioventricular (A-V) ring, cusps, chordae tendineae, and papillary muscles. The right ventricle contains three while the left ventricle contains only two papillary muscles, which are named according to their location. A thorough understanding of the normal anatomy as well as possible variations can help surgeons in various corrective surgeries involving papillary muscles. Material & methodsThe study included 50 formalin-preserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
1
0
0
1
Order By: Relevance
“…In thepresent work we adopted (Saha & Roy, 2018) criteria because we considered it as complete and clear evaluation of the PM morphological expression. We agree with (Saha & Roy, 2018;Bhadoria et al, 2022) and identified truncated as the most common APM shape (32 -66.2 %), followed by flattened (20 -27.8 %), conical (5.2 -15.6 %), bifurcated (8.9 -10.4 %) and trifurcated (<5 %). The conical shape of the MPP for (Saha & Roy, 2018) is the most frequent (45.8 %) while in the present study considering 121 total PPM the truncated shape is documented as having the highest incidence (36.4 %).…”
Section: Discussionsupporting
confidence: 87%
“…In thepresent work we adopted (Saha & Roy, 2018) criteria because we considered it as complete and clear evaluation of the PM morphological expression. We agree with (Saha & Roy, 2018;Bhadoria et al, 2022) and identified truncated as the most common APM shape (32 -66.2 %), followed by flattened (20 -27.8 %), conical (5.2 -15.6 %), bifurcated (8.9 -10.4 %) and trifurcated (<5 %). The conical shape of the MPP for (Saha & Roy, 2018) is the most frequent (45.8 %) while in the present study considering 121 total PPM the truncated shape is documented as having the highest incidence (36.4 %).…”
Section: Discussionsupporting
confidence: 87%
“…Нnatjuk et al, (2017), морфологам потрібно користуватися своїми кількісними параметрами серця, враховуючи вікові зміни. Тому, важливе значення у морфології, для визначення будови, форми, розмірів органів та систем, співвідношення їх специфічних структурних особливостей, має математичний аналіз структур морфологічних об'єктів, який здобув визнання як метод, що вирізняється об'єктивністю та достовірністю (Hryhorieva & Cherniavskyi, 2018;Bhadoria et al, 2022).…”
Section: результати та їх обговоренняunclassified